Optimizing Referral Services: A Health Management Approach to Quality Improvement in Health Services - Ramadhani, Felissia Shandra; Dewi , Nur Azizah Puspita; Safitri, Siti Salsabilla; Purwanti , Yuniar Setia; Humairo, Mika Vernicia (Tarqabin Nusantara Group, 2025)
Optimizing referral services through a health management approach aims to increase efficiency, reduce waiting times, and improve patient satisfaction. This study used a discrete-event simulation model with three scenarios: baseline (standard protocol), optimized service coordination (telemedicine integration), and predictive analytics-based resource reallocation. Simulation results showed a 40% reduction in waiting time (from 14 days to 8.5 days) in the service coordination scenario, with an increase in referral acceptance to 85%. Resource reallocation cut waiting time by 30% (9.8 days) and achieved 78% acceptance. Telemedicine expanded access to specialist services in remote areas, while predictive analytics reduced overload at major referral hospitals. However, challenges such as the primary-secondary care capacity imbalance and limited IT infrastructure in primary healthcare facilities still hamper. Recommendations include strengthening structured telemedicine, developing algorithm-based referral criteria, increasing primary care capacity, and dynamic feedback systems. This simulation proves that a holistic health management approach-combining technology, systemic collaboration, and data-driven policies-can build an adaptive, efficient, and equitable referral system.